Behavioral Drivers of Stock Market Participation: Insights from Ghanaian Investors - Banyen, Thadious (Journal of Business and Economic Options, 2022)
Understanding the complexities of stock market participation in Ghana is crucial for addressing the challenges associated with low participation rates. This study delves into the behavioral factors that influence individuals' decisions to engage in the stock market, aiming to provide actionable insights for policymakers and market participants. One key finding of this research is the significant impact of awareness of the stock market on participation levels. This underscores the importance of educational initiatives aimed at demystifying the stock market and empowering individuals to make informed investment decisions. Thus, the implementation of targeted public education campaigns could play a pivotal role in increasing awareness and understanding of the benefits and opportunities offered by the stock market. Moreover, trust emerged as another crucial determinant of stock market participation. Building trust in the market necessitates transparency, integrity, and effective regulation. Therefore, policymakers and market regulators should prioritize measures to enhance market integrity and investor protection, thereby fostering greater confidence among potential investors. Additionally, the study highlights the role of education in influencing stock market participation. By improving access to financial literacy programs and investment education, individuals from diverse socioeconomic backgrounds can be empowered to engage more actively in the stock market. Lastly, the research identifies herding behavior as a significant factor influencing stock market participation. This suggests the importance of social influences and peer networks in shaping investment decisions. Efforts to promote a positive investment culture and dispel misconceptions about the stock market could help counteract herding behavior and encourage more independent decision-making among investors. In conclusion, this study offers valuable insights into the behavioral drivers of stock market participation in Ghana and provides actionable recommendations for stakeholders. By addressing these factors and fostering a supportive environment for investment, we can work towards promoting broader and more inclusive participation in the stock market, ultimately contributing to the country's economic growth and development.